RELATIONSHIP OF VITAMIN D LEVELS AND GLYCEMIC CONTROL IN PATIENTS WITH TYPE 2 DIABETES MELLITUS.: http://doi.org/10.46536/jpumhs/2024/14.02.513 - Nazia Arain1 , Bashir Ahmed Khuhro2 , Mujahid Ali Chandio3 , Naveed Sattar Shaikh, Sadia Kazi5 , Bhagwani 6 . Shuja Anwar Kazi7, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
OBJECTIVE: To find out relationship between vitamin D levels and glycemic control in patients with type-2 diabetes mellitus (T2DM) STUDY DESIGN: Cross-sectional study. PLACE AND DURATION OF THE STUDY: The department of medicine at PMCH from January 2021 to December 2021. MATERIAL AND METHODS: A total of 195 T2DM patients of both genders aged 18 to 70 years were enrolled. All these patients were evaluated for their HbA1c levels along with 25 (OH)D levels. Demographical data along with clinical characteristics were recorded at the time of enrollment. All the patients were further divided in 2 groups as good glycemic control (GGC) as HbA1c below 7.0% or poor glycemic control (PGC) as HbA1c above or equal to 7.0% and compared in terms of demographic and laboratory parameters. RESULTS: Out of a total of 195 patients, there were 112 (57.4%) male. Overall mean age was noted to be 47.82+7.0 years. There were 138 (70.8%) patients having PGC while 57 (29.2%) had GGC. The 25 (OH)D was significantly low among patients with PGC versus GGC (p<0.0001). Significantly more patients with GGC had sufficient levels of 25 (OH)D in comparison to PGC (54.4% vs. 20.3%, p<0.00001). CONCLUSION: Poor glycemic control was found to have linkage with vitamin D deficiency while inverse relationship was seen between levels of HbA1c and vitamin D among patient having T2DM.